¿Retribucionismo solo para delitos de lesa humanidad? - Fernández Fiks, Tomás (2017)
In this paper I will hold that the decisions of both international and domestic criminal courts through which perpetrators of human rights abuses have been punished find their best justification in the theory of retributivism. To make this claim, I look at i) the language of those decisions, ii) the inapplicability of other justifications of punishment, iii) the value of our moral intuitions regarding the correctness of punishing human rights violations perpetrators. Once established the link between retributivism and punishment of the authors of crimes against humanity, I will sustain that retributivism should be defended for all crimes, arguing that this is the only way to preserve equality among victims.